An analysis of the causality relationship between economic growth and energy consumption: case study in Thailand - Pun Phullsub; Marpaung, Charles O.P.; Kumar, Sivanappan; Singh, Jai Govind; Shrestha, Rajendra Prasad; Royal Thai Government (RTG) (Pathum Thani, Thailand : Asian Institute of Technology, 2011)
The world energy is more powerful. Human is need energy not only consumption but also developing country by implementing in many sectors for example transportation and industrial sector. Although energy demand and economy growth trends are lookalike similarly but in detail they are not. Correlation is necessary but not sufficient for establishing a causal relationship. In this study the author uses time series data since 1971-2008 of Total Primary Energy Supply (TPES) and Gross Domestic Power Purchasing Parity (PPP) to analyze the causality relationship between energy consumption and economic growth in Thailand. The study uses Unit Root Test to test stationary of data and Causality Test by Granger to analyze relationship between two dependent variables. Form the result, TPES and PPP are cointegration and causality run from Gross Domestic Power Purchasing Parity (PPP) to Total Primary Energy Supply (TPES) only lag (1).
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 2011
Keywords: Energy consumption -- Economic aspects -- Thailand